Comparison of high-intensity focused ultrasound ablation for uterine fibroids with different blood flow grading based on Alder classification - Lijun Yang; Jun Liu; Siyun Wu; Yanhua Han; Jin Bai; Qiuling Shi (International Journal of Hyperthermia)
Objective This study aimed to evaluate the efficacy of ultrasound-guided high-intensity focused ultrasound ablation (USgHIFU) for uterine fibroids with different blood flow grading based on Alder classification.Materials and methods A total of 353 patients with solitary uterine fibroid who underwent USgHIFU from July 2014 to July 2019 were enrolled. The patients were classified as four groups based on blood flow grading in fibroids. The relevant factors influencing the therapeutic effect were analyzed.Results Significant differences were observed in treatment time, irradiation time, irradiation intensity, nonperfusion volume (NPV), NPV ratio and energy efficiency factor (EEF) among the four groups (p < 0.05). As the level of blood flow increased, the treatment time, irradiation time, irradiation intensity and energy efficiency factor (EEF) of USgHIFU were increased, but the NPV ratio was decreased. No major complication occurred in any patient of the four groups. Overall, 318 patients completed long-term follow-up, and 55 of 318 patients underwent re-intervention (17.2%). Univariate analysis indicated that increased menstruation, uterine volume, type of fibroids, signal intensity on T2-weighted imaging, NPV ratio were factors related to reinterventin (p < 0.05). Multivariate analysis revealed that the type of fibroids and NPV ratio were independent risk factors for re-intervention (p < 0.05).Conclusions Our results suggested that the difficulty of USgHIFU treatment for uterine fibroids could be evaluated using Alder classification. The fibroids with more blood flow were more difficulty to treat. However, satisfactory NPV ratio could be achieved even fibroids with abundant blood supply, and the long-term intervention rate was not increased.